Odpowiedzi

2010-04-11T17:31:18+02:00
A)2x-(-4-3x)=2x+4+3x=5x+4
b)10-2(t+1)=10-2t-2=8-2t
c)-3(2y+⅓)+4y = -6y-1+4y=-2y+1
d)-6(1-0,5u)+³/₂u=-6+3u+1½u=-6+4½u
e)2(3w-1)-(w+²/₂)=6w-2-w-1=5w-3
f)3a(a-2b)-5(b-2a)=3a²-2ab+5b+10a
2010-04-11T17:35:15+02:00
A)2x-(-4-3x)= 2x+4 + 3x= 5x+4
b)10-2(t+1)= -2t +8
c)-3(2y+1/3)+4y= -6y-1+4y= -2y-1
d)-6(1-0,5u)+3/2u=-6+ 3u+ 1 1/2u= 4 1/2u-6
e)2(3w-1)-(w+2/2)=6w-2-w-1=5w-3
f)3a(a-2b)-5(b-2a)=3a2-6ab-5b+10a

ta duża dwójka w ostatnim (f) jak masz napisane 3a2 to ta dwójka to jest kwadrat. tzn. ze 3a do kwadratu